Macroeconomic Impact on the Risk Profile of Islamic Commercial Banks in Indonesia - Fery Maulana Malik; Hamid Asayesh; Lalu Abu Gunawan; Ismail Pulungan (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
As a member of the G20, Indonesia has demonstrated economic stability with an average growth of 5.05% by 2024. Islamic commercial banks play an important role in supporting the national economy through Sharia-based financing, which is more stable than traditional banks. However, macroeconomic fluctuations such as inflation, GDP, BI rate, and exchange rates can impact Non-Performing Financing (NPF) as an indicator of credit risk. High NPF can affect the profitability and operational sustainability of Islamic commercial banks. Therefore, a deep understanding is required to maintain the stability of this sector. The aim of this study is to analyze the impact of macroeconomic factors on the NPF of Islamic commercial banks in Indonesia. With a quantitative approach using secondary data from quarterly reports for the period 2021-2023 and analyzed using multiple linear regression with panel data on nine Islamic commercial banks that meet the criteria, namely Bank Aladin Syariah, Bank Victoria Syariah, Bank Jabar Banten Syariah, Bank Panin Dubai Syariah, Bank Mega Syariah, Bank BCA Syariah, Bank BTPN Syariah, Bank Syariah Indonesia, and Bank Muamalah Indonesia. The findings indicated that inflation exerts a substantial impact on Non-Performing Financing (NPF). Conversely, Gross Domestic Product (GDP), Bank Indonesia (BI) rate, and exchange rate do not exhibit any influence on NPF. Nevertheless, concurrently, inflation, GDP, BI rate, and exchange rate collectively demonstrate a significant effect on NPF. This suggests that these variables interact with one another and play a role in altering the quality of financing extended by Islamic commercial banks.